Jornal na escola: conhecimento e auto-estima - Campanhão, Izilda Bueno Barrios (Comunicação & Educação, 2000)
An elementary school teacher, from the Vale do Ribeira region, in São Paulo, reports on an experience carried out with fourth-grade students, who, by manipulating newspapers, researching and exercising with verbal languages (informative), both graphic and plastic, produced the Classroom Newspaper (Jornal da classe) and the Sugarcane Newspaper (Jornal da cana), the main economic activity in the region. The multidisciplinary work contributed to student involvement with building knowledge in a happy and creative manner. The results demonstrate that the students profited well and that their self-esteem went up because of the project.